Characterization of blood-brain barrier integrity in a B-cell-dependent mouse model of multiple sclerosis - Bell, Luisa; Koeniger, Tobias; Tacke, Sabine; Kuerten, Stefanie (Histochemistry and Cell Biology, 2019)
Recent studies with B-cell-depleting antibodies have demonstrated clinical success in the treatment of multiple sclerosis (MS) patients. While these antibodies efficiently target B cells in the blood, it is unclear how effective they are in the central nervous system (CNS), especially in the context of limited blood-brain barrier (BBB) permeability and the ongoing discussion on the relevance of B-cell aggregate formation in the brains of SP-MS patients. The aim of this study was to evaluate BBB integrity in the context of B-cell-dependent neuroinflammation in a mouse model of MS. C57BL/6 mice were actively immunized with either myelin oligodendrocyte glycoprotein peptide 35-55 to induce T-cell-dependent experimental autoimmune encephalomyelitis (EAE), or with the myelin basic protein-proteolipid protein fusion protein MP4 for additional B-cell dependence. BBB integrity was assessed using Evans Blue or fluorescein isothiocyanate-dextran injection, respectively, in combination with immunofluorescence staining for key components of the BBB. In both EAE models, tracer leakage into the CNS parenchyma was observed indicating BBB leakiness. Yet, intensity and distribution patterns of leakage differed between the two models. There was no difference in the severity of BBB damage comparing acute and chronic MP4-induced EAE, but the formation of B-cell aggregates was associated with local BBB impairment in this model. This study underscores that a leaky BBB is a characteristic feature of EAE, but it also suggests that extent and region specificity of BBB damage differs between individual EAE models that vary in the underlying immunopathology.
CRIS-Team WoS Importer:2019-06-18